2022
DOI: 10.1021/acs.nanolett.1c04969
|View full text |Cite
|
Sign up to set email alerts
|

All-State Switching of the Mie Resonance of Conductive Polyaniline Nanospheres

Abstract: Polyaniline (PANI), a conductive polymer, is a promising active material for optical switching. In most studies, active switching has so far been realized only between two states, whereas PANI has a total of six states. The optical properties of nanoscale PANI in all six states have remained unclear. Herein we report on all-state switching of the Mie resonance on PANI nanospheres (NSs) and active plasmon switching on PANI-coated Au nanodisks (NDs). All-state switching of differently sized PANI NSs is achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…460 nm was the scattering peak of PANI. 29 Therefore, the above results proved the potential of the Au@PANI nanoprobe for single-particle studies based on Rayleigh scattering under DFM.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…460 nm was the scattering peak of PANI. 29 Therefore, the above results proved the potential of the Au@PANI nanoprobe for single-particle studies based on Rayleigh scattering under DFM.…”
Section: Resultssupporting
confidence: 59%
“…[26][27][28] In general, PANI exists in six different states, namely pernigraniline salt (PS), pernigraniline base (PB), emeraldine salt (ES), emeraldine base (EB), leucoemeraldin salt (LS), and leucoemeraldin base (LB). 29 The switch between all these states can be realized by protonation/deprotonation and applying electrochemical potential. 30 Wang's group systematically investigated the plasmonic switching behavior of (Au nanorod core)/(PANI shell) nanostructures, and found that the plasmon resonance of the Au core can be modulated reversibly by varying the dielectric function of the PANI shell through proton doping.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that PANI can exist in six states with different refractive indices at various pH values and redox states: leucoemeraldine base (LB), leucoemeraldine salt (LS), emeraldine base (EB), emeraldine salt (ES), pernigraniline base (PB), and pernigraniline salt (PS). 51 The conditions or means to accomplish the full state transformation are often severe, such as strong acidic environments, changes in aqueous and non-aqueous electrolyte environments, and higher potentials, which will directly affect the lifetime of the materials. In contrast, ES (n ES ≈ 1.40), PB (n PB ≈ 2.05), and LB (n LB ≈ 1.68) can be transformed in a relatively gentle manner.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Mie resonance has recently been found by our group to be supported by conductive PANI NSs. The Mie resonance supported by organic conductive PANI NSs can be reversibly tuned and switched on and off among the six states of PANI . The six different states of PANI include leucoemeraldine base (LB), leucoemeraldine salt (LS), emeraldine base (EB), emeraldine salt (ES), pernigraniline base (PB), and pernigraniline salt (PS).…”
Section: Dielectric Electromagnetic Resonance In Conductive Polymersmentioning
confidence: 99%
“…Organic conductive polymers had not been thought of before for supporting electromagnetic resonance owing to their low refractive indexes and small charge carrier concentrations. Conductive polymers have been considered as an emerging type of electromagnetic resonator recently. They can conduct charges through the conjugation of their alternate single C–C and double CC bonds along the polymer backbone, which makes conductive polymers possess unique electronic and optical properties. There are many types of conductive polymers, including polyaniline (PANI), polypyrrole, and poly­(3,4-ethylenedioxythiophene) (PEDOT) .…”
Section: Introductionmentioning
confidence: 99%